How Microgrids Enhance Disaster Management: Three Case Studies Examining Economic, Legislative and Infrastructural Foundations - Mammadova, Hamida; Mirzayeva, Fidan; Barcenas Ornelas, Diego (My University, 2026)
This capstone paper evaluates the legislative, economic, and technical feasibility of integrating decentralized microgrid systems into the national energy framework of the Republic of Azerbaijan to enhance disaster management and electricity grid resilience. Due to its dependence on a centralized and vertically integrated power model managed by state monopolies Azerenerji and Azerishiq, Azerbaijan’s grid infrastructure faces structural vulnerabilities in the presence of unpredictable disaster shocks. This structure presents a critical “single point of failure” where one failure (whether technical or human) in the grid can result in nationwide intermittent or absolute blackouts. This study evaluates the structural bottlenecks through three analytical lenses: legislative gaps in prosumer codification, market distortions and cost-recovery limitations under regulated tariffs, and the technical limitations within the transmission grid. The empirical basis of this research is based on secondary international data sources as well as primary qualitative data which was conducted through eight semi-structured interviews from sector experts and stakeholders representing the Ministry of Energy of Azerbaijan, SOCAR Green, AERA, BP, Nobel Energy and AGAS. The study conducts the comparative analyses of international case studies, deriving on legislative insights from Puerto Rico, technical pilot structures from Japan, and comparing the economic framework of the gains from the financial system of Peru to the centralized system failure in Cuba. The evaluation applies four policy alternatives against five criteria: effectiveness, efficiency, equity, feasibility and political acceptability, to analyze and select the most optimal policy alternative pathway.
Keywords: microgrids; energy resilience; decentralization; grid modernization; prosumer; Azerbaijan Energy Policy